1997
DOI: 10.1016/s0014-5793(97)00618-2
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Staphylococcus aureusγ‐hemolysin into a pore‐forming ring‐shaped complex on the surface of human erythrocytes

Abstract: Staphylococcal y-hemolysin consists of Hlgl (or Luk F) of 34 kDa and Hlg2 of 32 kDa, which cooperatively lyse human erythrocytes. Since y-hemolysin caused swelling of human erythrocytes prior to lysis, we studied pore-forming nature of the toxin by use of polyethylene glycols as osmotic protectants and determined the functional diameter of the pore. To elucidate the molecular architecture of the membrane pore formed by yhemolysin, we solubilized the pore complex with 2% sodium dodecyl sulfate, separated it fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 16 publications
8
70
0
Order By: Relevance
“…The data indicated that Hlg forms a high-molecular-sized complex(es) of approximately 200 kDa, which contain LukF and Hlg2 at a molar ratio of 1:1 on the surface of human erythrocytes. 28) It was also shown that the preceding binding of LukF is essential for complex formation as well as for Hlg2 binding under the physiologically relevant conditions. 29) Recently, we found that LukF binds strongly to membranes with a binding constant (K F ) of 2:1 Â 10 À4 m À2 and a large number of binding sites (R F ) of 2:0 Â 10 4 m À2 , and that Hlg2 also binds to membranes with a lower binding constant (K H = 1:2 Â 10 À5 m À2 ) combined with a similar number of binding sites (R H , 1:8 Â 10 4 m À2 ), indicating an approximately 18-fold decrease in the extent of binding of Hlg2 compared with that of LukF.…”
mentioning
confidence: 99%
“…The data indicated that Hlg forms a high-molecular-sized complex(es) of approximately 200 kDa, which contain LukF and Hlg2 at a molar ratio of 1:1 on the surface of human erythrocytes. 28) It was also shown that the preceding binding of LukF is essential for complex formation as well as for Hlg2 binding under the physiologically relevant conditions. 29) Recently, we found that LukF binds strongly to membranes with a binding constant (K F ) of 2:1 Â 10 À4 m À2 and a large number of binding sites (R F ) of 2:0 Â 10 4 m À2 , and that Hlg2 also binds to membranes with a lower binding constant (K H = 1:2 Â 10 À5 m À2 ) combined with a similar number of binding sites (R H , 1:8 Â 10 4 m À2 ), indicating an approximately 18-fold decrease in the extent of binding of Hlg2 compared with that of LukF.…”
mentioning
confidence: 99%
“…As shown by white arrowheads, several pores in the cluster are anchored to a part of the membrane. In our previous study, the diameter of Hlg pores was estimated to be approximately 2 nm [5], which is smaller than that of hemoglobin. However, hemoglobin seems to easily pass through the large hole around the cluster.…”
Section: Resultsmentioning
confidence: 87%
“…Removal of non-bound Hlg and incubation were performed as described in Section 2.1. The amount of potassium ions from the Hlg-treated erythrocytes was measured as described previously [5].…”
Section: Efflux Of Potassium Ions From Hlg-treated Hementioning
confidence: 99%
See 2 more Smart Citations